Memorable tourism experience in the context of astrotourism - Rodrigues, Áurea (2022)
Astrotourism involves a variety of activities carried out during the night, requiring a deeper knowledge about the cognitive and emotional process that the tourist has and that leads to a memorable experience and loyalty. This study explores how (i) astrotourism stimuli are associated with cognitive states, designed by knowledge and involvement, (ii) cognitive states increase emotional states, represented by hedonism and refreshment, and (ii) emotional states generate responses, such as recommendation and loyalty. This study contributes to extending the S (stimulus) -O (organism) -R (response) framework by integrating cognitive appraisal theory and incorporating stimuli, cognitive and emotional states not used in the previous research. Recommendations for astrotourism destination managers are also discussed.